A bottom-up method to construct Ru-doped FeP nanosheets on foam iron with ultra-high activity for hydrogen evolution reaction. (8th February 2023) - Zhang, Xinglong; He, Yulin; Zhu, Bin; Wan, Xinming; Hua, Shiyang; Tang, Hui
Abstract: As a clean, high calorific value and renewable energy, hydrogen is considered to be an ideal green energy to replace traditional fossil energy. Among various methods for preparing hydrogen, electrolytic water hydrogen evolution has attracted the attention of researchers because of its high efficiency, easy separation of products and green and pollution-free advantages. In this experiment, starting from the porous foam iron, Fe2 O3 nanosheets are obtained by anodic oxidation, and then the material is phosphated by in-situ phosphating in a tubular furnace to obtain FeP nanosheets. Finally, the Ru dopants are deposited into the lattice of FeP nanosheets by electrodeposition to obtain the Ru-doped FeP nanosheets. Through the characterization of morphology and the test of electrocatalytic hydrogen evolution performance, the Ru-doped FeP nanosheets show ultra-high electrochemical hydrogen evolution activity and have regular nanosheets array structure. Graphical abstract: Image 1 Highlights: A bottom-up method is reported to synthesize Ru-doped FeP nanosheets which are regularly grown on Fe foam. Ru-FeP@Fe foam catalysts exhibited ultra-high activity in HER. Ru-FeP@Fe foam exhibited ultra-high active specific surface area. This work provides a reference for developing the field of electrocatalytic hydrogen evolution with iron-based materials.